The influence of group-level factors on individual energy-saving behaviors in a shared space: The case of shared residences. (15th August 2021) - Zhu, Jiaolan; Alam, Md Morshed; Ding, Zhikun; Ekambaram, Palaneeswaran; Li, Jie; Wang, Jiayuan
Abstract: In business and service buildings, shared spaces constitute large areas where occupants share energy resources and manage them. Changing people's behaviors toward conscious and efficient energy use within shared spaces has great potential to conserve energy and reduce greenhouse gas emissions. The occupants in a shared area closely interact with each other and their energy use behaviors have a higher probability of being influenced by the group environment. Although the significant role of groups in occupant behavior has been highlighted in some studies, little is known about how group environments affect individual energy-saving behaviors in a shared space. This study explored the influencing mechanism of group-level factors on individual energy-saving behavior in a shared space and developed a theoretical model based on dynamic group theory. A literature review was carried out to identify group-level factors that may influence individual energy-saving behavior. An empirical study was conducted in the shared space contextualized in college student residences in Zhuhai, China, to understand the mechanism of how the group-level factors influence individual energy-saving behaviors. Data collected from the questionnaire survey was analyzed through structural equation modeling. The results showed that descriptive norms i.e., actions of other group members, have the highest impact on individuals' energy saving behavior in a shared space. Interestingly, any direct feedback or suggestions provided to an individual to save energy has a very minimum influence on individuals' energy-saving behavior. In shared spaces, what others actually do is more influential in motivating individuals to engage in energy-saving behaviors than any energy-saving instructions given to an individual. Group interaction is conducive to increasing the visibility of descriptive norms and thus strengthening individuals' behavioral intention for energy saving. These findings will contribute to developing energy-saving strategies in a shared space focusing on 'descriptive norms', replacing the current instruction-based approach. Besides, the empirical research findings could provide a guideline for policy makers to develop behavioral change strategies regarding energy conservation. Highlights: Influence of group-level factors on individual energy-saving behaviors were examined. Group dynamic theory was applied to understand the behavior influencing mechanism. Group descriptive norms have the highest influence on personal energy-saving behavior. Group interaction is conductive to increase the visibility of descriptive norms. Action is more influential than words to promote individual energy-saving behaviors.